2021
DOI: 10.3390/ijms22052419
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Aging and Age-Related Diseases (CVD and Neurological) Due to Air Pollution and Traffic Noise Exposure

Abstract: The World Health Organization estimates that only approximately 25% of diversity in longevity is explained by genetic factors, while the other 75% is largely determined by interactions with the physical and social environments. Indeed, aging is a multifactorial process that is influenced by a range of environmental, sociodemographic, and biopsychosocial factors, all of which might act in concert to determine the process of aging. The global average life expectancy increased fundamentally over the past century,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 179 publications
(223 reference statements)
0
25
0
Order By: Relevance
“…Oxidative stress and inflammation represent the common denominator of the adverse cardiorespiratory health effects of air pollution. Recent evidence from human and animal studies suggests that exposure to multiple air pollutants may have the potential to increase systemic oxidative stress and inflammation, both relevant to mediating disease risk (reviewed in [ 16 , 17 ]). However, understanding the complete picture of underlying pathomechanisms is still ongoing, and complex interactions with other risk and lifestyle factors, such as physical activity, are very likely.…”
Section: Pathomechanisms Of Air Pollution With Focus On Oxidative Stress and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and inflammation represent the common denominator of the adverse cardiorespiratory health effects of air pollution. Recent evidence from human and animal studies suggests that exposure to multiple air pollutants may have the potential to increase systemic oxidative stress and inflammation, both relevant to mediating disease risk (reviewed in [ 16 , 17 ]). However, understanding the complete picture of underlying pathomechanisms is still ongoing, and complex interactions with other risk and lifestyle factors, such as physical activity, are very likely.…”
Section: Pathomechanisms Of Air Pollution With Focus On Oxidative Stress and Inflammationmentioning
confidence: 99%
“…In contrast, practically no evidence is available concerning the joint effects of physical activity and air pollution on mental health. Besides the proposed biological effects centered on oxidative stress and inflammatory processes (that are also involved in the pathogenesis of mental disorders [ 16 , 17 ]), high levels of air pollution may also affect mental health through interference with health related behaviors such as less outdoor physical activity with face to face social contact, which represents an effective way to cope with mental health related stressors [ 8 ]. Interestingly, a recent study found lower PM 10 exposure to be associated with life satisfaction, more self-esteem, and higher stress resilience in 3020 German adults [ 112 ].…”
Section: Recent Epidemiological Evidence On the Association Between Physical Activity Long Term Exposure To Air Pollution And (Cardiovascmentioning
confidence: 99%
“…The problem of noise in the underwater environment was discussed at the 19th meeting of the United Nations Open-ended Informal Consultative Process on Oceans and the Law of the Sea (ICP- 19) where the negative consequences of the impact of anthropogenic noise on aquatic life were noted, including disruption of communication between individuals, displacement of animals from their breeding and feeding grounds, and the occurrence of stress and disease leading to death [1]. Ship noise is considered the most widespread continuous underwater pollutant, and it can completely dominate low-frequency (up to 500 Hz) soundscapes in heavily trafficked areas [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The higher-stress situations may have maladaptive or negative consequences (distress), including pathogenic effects [19]. It is also worth noting that the consequences of prolonged stress are particularly deleterious due to energetic costs associated with coping with the stress response (allostatic load), negatively affecting other vital functions, including reproduction [20] and enabling changes at the population and species levels [9,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation